Optimization of detection of circulating tumor cells by flow cytometry and qRT-PCR - Pogoda, Katarzyna; Rybojad, Paweł; Álvarez, Inés Ramírez; Mohanathas, Thusyanthan; Hosseini, Sarah; Tabarkiewicz, Jacek (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Treatment and diagnostic process in solid tumors like lung cancer are still based on invasive methods such as bronchoscopy, solid biopsy et cetera. One of the less invasive methods is a proposed “liquid biopsy” which is based on capturing of tumor cells circulating in the blood. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to standardize conditions and to assess the sensitivity of the identification of circulating tumor cells (CTCs) with the use of flow cytometry and qRT-PCR. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In the first model of CTCs, cells from the A549 lung cancer cell line were suspended in 1 ml of healthy donors’ blood in 5 spikes increasingly: 0, 10, 50, 100 and 200 and the cells were detected in flow cytometer. In the second model, cells from the A549 and H1975 lung cancer cell lines were used. Spikes were prepared as in the first model, but cells were suspended in 400 µl of healthy donors’ blood and were detected with the use of qRT-PCR. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. An increasing number of detected cytokeratin positive events from the 1st spike “0” to the last one - “200” was observed by flow cytometry. Median value in the negative control was 0 false positive cells. In tubes from “10” to “200” the median was 5, 43.5, 58 and 78, respectively. Mean sensitivity of flow cytometry was 63.79%. In qRT-PCR, correlation between increasing number of sorted cells in several spikes and the level of mRNA expression for KRT19 gene was not observed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Commonly available methods like flow cytometry and qRT-PCR seem to be attractive solutions for CTCs detection, but they need pre-enrichment procedures and standardization.